Development of the performance structure model in snowboard slopstyle and bigair - Ozaki, H.; Inaba, Y.; Kimura, A.; Yamamoto, Y. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: The performance structure model (PSM) is one of the better tools when considering the structure of sport. The model aims to provide a comprehensive framework for evaluating and supporting athletes, ensuring they receive the necessary training and resources to excel in competitive environments. We therefore built a PSM for Snowboard Slopestyle Big Air (SSBA) before providing scientific support to the Japanese National SSBA Team.